Fiscal policy and structural reforms in transition economies: An empirical analysis - Jukka Pirttilä (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
This paper makes an empirical examination of the relationship between fiscal balance and structural reforms using panel data from 25 transition economies The results indicate that price liberalisation has a positive impact on fiscal performance, while privatisation and restructuring, via unemployment, affect the fiscal balance negatively.These findings are somewhat in contrast with earlier empirical work and theoretical transition economics that maintain fiscal pressures are most severe in fast-reforming countries.The analysis further suggests that countries with better fiscal positions may have benefited from favourable initial conditions.
URN:NBN:fi:bof-201408072055
Keywords: 330